The telegraph proposal - Welborn, Gina; Whitham, Becca (Montana brides romance, 2019)
With the help of the Archer Matrimonial Company, Yancey Palmer has finally put Hale Adams, the man she<U+2019>s loved for ten years<U+2014>sometimes not wisely or well<U+2014>behind her. Yancey is so sure of her love for the man the agency matched her with, she readily promises a friend that she<U+2019>ll help Hale with his mayoral campaign without chasing him. Hale has also engaged the services of the matrimonial agency. He<U+2019>s so pleased with one lady, he requests that she join him in Helena to commence a sixty-day courtship. But instead, the Archer ladies arrive in town to reveal the true identities of both Hale<U+2019>s and Yancey<U+2019>s matches: each other. Can they look past their misunderstandings and hurt to see that they are still a perfect match?